Peningkatan Kemampuan Pemecahan Masalah Matematis dengan Cooperative Script dan Blended Learning - Rahmawati; Anggria Septiani Mulbasari (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
The purpose of this research wasto find out the improvement of students' mathematical problem solving abilities that were taught by using Cooperative Script Model and Blended Learning. Cooperative script is a learning model by conveyinglearning material starting with sharinga summary of teaching material and then providing the opportunityfor the studentsto read it for a moment and sharingnew ideas into the teaching material provided alternately with each other's partners. The subjects in this studywere 60 students ofMA.Al-Fatah Palembang. The quasi-experimental method used in this study with the test asinstrument in collectingthedata which were thenanalyzed quantitatively using the t-test statistical formula. Based on the result of the calculation, it was found that the average test score of students treated by using cooperative script learning modelwerebetter than those treated by using conventional learningmodel.